Penetapan Hari Pernikahan Berdasarkan Tradisi Jujuran - Sitompul, Elma Ariska; Nasution, Muhammad Arsad (Jurnal El-Thawalib, 2021)
Marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. In Islamic marriage law, there is a principle known as the principle of selectivity.The problems in this thesis are how to determine the wedding day based on the Jujuran tradition in Hutabalang Village, and How to Review Islamic Law on the determination of the wedding day based on the Jujuran tradition in Hutabalang Village. The purpose of this study was to determine the implementation of determining the wedding day based on the Jujuran tradition in Hutabalang Village, and to analyze the Islamic Law Review on the determination of the wedding day based on the Jujuran tradition in Hutabalang Village, Badiri District, Central Tapanuli Regency.This type of research is field research using qualitative descriptive analysis method. This research approach is by means of observation, interviews, documentation based on the provisions of Islamic law and applicable customary law relating to the determination of a wedding day based on the jujuran tradition in Hutabalang Village, Badiri District, Central Tapanuli Regency. As for what the researchers studied were traditional leaders, religious leaders, and communities who determined their wedding day based on the jujuran tradition.The results showed that "The determination of the wedding day based on the tradition of honesty in Hutabalang Village, Badiri District, Central Tapanuli Regency in terms of Islamic law". Marriage can be done in the month of Rabiul Akhir, Jumadil Akhir, Rajab, Syaban, then looking for a good day of marriage with a period of one week or one week. There are five people who are not allowed to marry, namely Rupput Tuju, Simonggal-monggal, Unang Lao, Unang Lao, and Doppak Pudi Pamudunna, ni Parhohos logi balloons. After the wedding day is set for the bride and groom, the designated date is for marriage so that there are no disturbances faced at the time of a wedding. The implication of this tradition is that doubts if it does not comply with the inherent customs and becomes a belief, it is feared that unwanted things will occur. This kind of tradition is not in accordance with Islamic law because it is feared that it will fall into kufr. In this case the rule of fiqhiyyah applies "Refusing damage takes precedence over attracting benefit."